Mental Workload and Job Satisfaction in Healthcare Workers: The Moderating Role of Job Control - Rostami, Fatemeh; Babaei-Pouya, Amin; Teimori-Boghsani, Gholamheidar; Jahangirimehr, Azam; Mehri, Zahra; Feiz-Arefi, Maryam (Frontiers in Public Health, 2021)
The aim of this study was to investigate the moderating role of job control in relation to mental workload and job satisfaction of healthcare workers.This descriptive-analytical study was carried out on 480 nurses, midwives, and administrative workers in four educational hospitals of Ardabil, Iran. Research tools were included demographic information questionnaire, NASA-TLX questionnaire, job description index (JDI) questionnaire and job control inquiry. Compared with administrative workers, mental workload of nurses and midwives was significantly higher and likewise mental workload of nurses was significantly difference compared to midwives (P < 0.001). Nurses and midwives had substantially higher job satisfaction than administrative workers (P < 0.001). Also, nurses and midwives had higher job control than administrative workers (P < 0.001 & P = 0.002, respectively). Based on the designed model, the correlation between mental workload and job satisfaction was negative and significant. (r = -0.22); which in the presence of job control, the relationship between the two variables of workload and job satisfaction slightly increased (r= -0.19, p < 0.001). These conditions were the same in the three job groups separately. Mental workload is inversely related to job satisfaction and job control. Job control plays an important role in improving working conditions in healthcare workers.